Comparison of red-shifted firefly luciferase Ppy RE9 and conventional Luc2 as bioluminescence imaging reporter genes for in vivo imaging of stem cells - Liang, Yajie (Society of Photo-Optical Instrumentation Engineers, 2012)
One critical issue for noninvasive imaging of transplanted bioluminescent cells is the large amount of light absorption in tissue when emission wavelengths below 600 nm are used. Luciferase with a red-shifted spectrum can potentially bypass this limitation. We assessed and compared a mutant of firefly luciferase (Ppy RE9, PRE9) against the yellow luciferase luc2 gene for use in cell transplantation studies. C17.2 neural stem cells expressing PRE9-Venus and luc2-Venus were sorted by flow cytometry and assessed for bioluminescence in vitro in culture and in vivo after transplantation into the brain of immunodeficient Rag2-/- mice. We found that the luminescence from PRE9 was stable, with a peak emission at 620 nm, shifted to the red compared to that of luc2. The emission peak for PRE9 was pH-independent, in contrast to luc2, and much less affected by tissue absorbance compared to that of luc2. However, the total emitted light radiance from PRE9 was substantially lower than that of luc2, both in vitro and in vivo. We conclude that PRE9 has favorable properties as compared to luc2 in terms of pH independence, red-shifted spectrum, tissue light penetration, and signal quantification, justifying further optimization of protein expression and enzymatic activity.